The Influence Of Education Level, Work Motivation, And Work Discipline On Employee Performance - Nurlina Nurlina; Hardinalis Kobal (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
The study explores how much influence the Level of Education, Work Motivation, and Work Discipline have on the performance of PT KSP Makmur Mandiri Employees. The research method is quantitative descriptive. The sampling technique uses a total sampling of 128 people. Data sources are secondary data and primary data. The analysis method uses multiple Linear Regression, t-test, F-test, and Determination Coefficient test with the help of SPSS V.26.0. From the results of data processing, multiple linear regression is obtained Y = 16,835 + 0.285X1 + 0.160X2 + 0.138X3 +e. The results of the t-test for Education Level (X1) are t-count > t-table (3,063 > 1.660) and the value (sig = 0.003 < 0.05), so Ho is rejected and H1 is accepted. The t value of the Work Motivation variable (X2) is tcount>ttable (2,460>1,660) and the value (sig = 0.015<0.05), so Ho is rejected and H2 is accepted. The t count value of the work discipline variable is tcount>ttable (3,323>1,660) and the value (sig = 0.001<0.05), so Ho is rejected and H3 is accepted. The F test results obtained Fcount>Ftable, (27,467>2,305, with a significance value of 0.000 (p<0.05), so Ho is rejected and H4 is accepted. The results of the determination coefficient show an Adjusted R Square (R2) value of 0.385, meaning that 35.5% of the independent variable can explain the dependent variable, the remaining 65.5% is explained by other variables not discussed in this study.